Consequences of EU Accession: Economic Effects on CEECs - Michael Landesmann; Sandor Richter (The Vienna Institute for International Economic Studies (wiiw), 2003)
This paper discusses the economic effects of EU enlargement for the group of Central and East European accession countries (ACs). It consists of three parts In Part A the financial aspects of accession to the EU are explained. It deals firstly with the outcome of the negotiations at the December 2002 European Council Summit in Copenhagen in relation to the expected flows of net transfers over the period 2004-2006. The most uncertain component of these transfers are related to the project-related funds, their disbursement and fiscal implications because of co-financing requirements. Secondly, we discuss the issue of the longer-run negotiations with respect to the Financial Framework to be decided for the period 2007-2013, here the issue of the formation of likely new coalitions within the enlarged European Union is dealt with and possible winners and losers in such negotiations are identified. In Part B we discuss the difficulties the new members will face upon accession in the conduct of macroeconomic policy. In particular, the crucial issue of fast vs. delayed entry to the European Monetary Union (EMU) will shape the constraints within which the conduct of fiscal and monetary policy will have to take place. It is quite likely that it is this issue which will dominate the medium-run growth prospects of the new members upon accession. Part C explores the longer-run growth and convergence scenarios for the new member states. It describes the relative growth performance of the ACs in relation to the EU so far and discusses the reasons why the growth performances might remain more volatile compared to those of the current EU member countries.
Keywords: E52; E61; E63; F14; F15; F36; 330